Synchronous Operable Pancreatic and Breast Cancer Without Genetic Mutation: A Literature Review and Discussion - Ofri, Adam; Zuidersma, Danika; Diakos, Connie I.; Stevanovic, Amanda; Wong, Matthew; Sood, Samriti; Samra, Jaswinder S.; Gill, Anthony J.; Mittal, Anubhav (Frontiers in Surgery, 2022)
Background Synchronous cancers are rarely detected when working-up a patient for a primary cancer. Neoadjuvant management of synchronous breast and pancreatic cancers, without a germline mutation, has yet to be discussed. Two patients were diagnosed with synchronous breast and pancreatic cancers at our institution over the last decade. Results The first patient was 61-years old and diagnosed with a HER2+ breast cancer. The second patient was 77-years old and diagnosed with a Luminal B breast cancer. The inability to provide concurrent breast and pancreatic neoadjuvant therapy for the HER2+ patient, resulted in upfront surgery. The second patient was able to have both cancers treated simultaneously - neoadjuvant chemotherapy to the pancreas, and neoadjuvant endocrine therapy to the breast. Discuss There is no single neoadjuvant regimen that treats both pancreatic and breast cancer. The differences in breast cancer sub-types greatly impacted our neoadjuvant options. Our recent experience led us to the hypothesis that breast cancer care dictates treatment, while pancreatic cancer determines survival.